Extraction, Microbial Load and Acute Toxicity Determinations of the Exudate Gum of Anacardium occidentale - A Potential Excipient in Drug Delivery - Ologunagba , M. O.; Azubuike, C. P.; Silva , B. O. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Natural polymers are increasingly used as excipients in formulation systems over the synthetics due to their comparative advantages. Exudate bark gum of Anacardium occidentale (family: Anacardiaceae) has been suggested for its potential usefulness in drug delivery systems. Characterizations of material substances are an integral part of excipient development. This study sought to extract Anacardium occidentale gum (AoG) from the crude exudate and determine its microbial load and acute toxicity using established methods and official guidelines. Data were expressed as mean Standard Error of the Mean (± SEM) and were statistically analyzed using one-way Analysis of Variance (ANOVA); level of significance was set at (P < 0.05). High yield, 72% w/w of the extracted gum was achieved. Microbial evaluation revealed the absence of objectionable organisms such as Salmonella species, Shigella species, Proteus species, Staphylococcus aureus, Escherichia coli, Klebsiella species, Pseudomonas aeruginosa, Vibrio cholera and Bile Tolerant Gram-Negative bacteria. Total aerobic microbial, yeast and mould counts were 1.70x10² and 6 x101 respectively. These values did not exceed the microbial limits specified by the United States Pharmacopoeia. LD50 value greater than 5000 mg/kg was obtained. There was no observance in the experimental animals of any morbidity, mortality or signs of acute toxicity, treatment related abnormalities on the body weights, haematological parameters and organs histopathology at all the administered doses. There was no significance on these parameters between the control and AoG tested groups. AoG microbial and acute toxicity profiles have suggested its safety and potential excipient usefulness in formulation systems such as drug delivery.